Pengaruh Brand Image Perpustakaan terhadap Keputusan Berkunjung Pemustaka di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Hayati, Jaza; Nabila, Jeihan (ARZUSIN, 2024)
The aim of this research is to describe whether there is an influence of brand image on users' visiting decisions at the Archives and Library Service of West Sumatra Province. The type of research used is quantitative research with a descriptive approach. The population in this research is all users who visit the West Sumatra Province Archives and Library Service in 2023, namely 48,759 people. The sampling technique used was simple random sampling. The number of samples in this research was 100 samples. In this study, researchers used a questionnaire as an instrument. The data collection technique was carried out by distributing questionnaires to all research samples. The results of this research show that: first, brand image has a total average score of 4.28 which is categorized as very good. So it can be said that the library brand image at the West Sumatra Province Archives and Library Service is very good for users. Second, the decision to visit has a total average score of 4.35, which means it is classified as very good. So it can be said that the user's decision to visit the brand image is very good for the user. Third, the library brand image has an influence of 31.3% on the decision to visit users at the Archives and Library Service of West Sumatra Province, while the remaining 68.7% is influenced by other factors not examined in this research.